1989
DOI: 10.1002/nme.1620280514
|View full text |Cite
|
Sign up to set email alerts
|

Numerical solution of linear two‐point boundary problems via the fundamental‐matrix method

Abstract: SUMMARYA numerical method is presented for the solution of linear systems of differential equations with initialvalue or two-point boundary conditions. For y ' ( x ) = A(x)y(x) + f(x) the domain of interest [ a, 61 is divided into an appropriate number L of subintervals. The coefficient matrix A(x) is replaced by its value Ak at a poirir XA within the kth subinterval, thus replacing the original system by the L discretized systems yB(x) = Akyk(x) + fk(x), k = 1,2, ._., I,. The fundamental matrix solution @k(x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…These equations constitute a two-point boundary problem that is solved numerically by using the fundamental matrix method [8]. Comparison is made with the characteristic matrix method [11].…”
Section: Derivation Of Coupled-mode Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These equations constitute a two-point boundary problem that is solved numerically by using the fundamental matrix method [8]. Comparison is made with the characteristic matrix method [11].…”
Section: Derivation Of Coupled-mode Equationsmentioning
confidence: 99%
“…In this paper, we study the influence of grating strength and chirp parameter on chirped grating response by using the method of multiple scales [7] and employ the fundamental matrix method [8] to solve the resulting coupled-mode equations numerically. Work on apodized unchirped reflection gratings [9] using these two methods showed that the coupled-amplitude equations of coupled-mode theory were insufficiently accurate in predicting the spectral response, especially when the strength of the periodic index perturbation ( ) increases beyond = 0.1.…”
Section: Introductionmentioning
confidence: 99%
“…To solve the linear parts of equations (1) and (3) for the coupled vibration modes and frequencies, we make use of the state-space concept and the fundamental-matrix method [13]. To this end, we assume that v(s, t) = V(s)e zot and 7(s, t) = C(s)e i~t .…”
Section: Equations Of Motion and Linear Eigensolutionsmentioning
confidence: 99%
“…jlw21313, A64 -11313 A65 -jlw2 A46 -/~11 -/~213 /311 ' /~11 " (15) According to the fundamental-matrix method [13], the solution of equation (13) can be expressed in the general form Figures 2(a) and 3. The linear mode shapes and their corresponding frequencies for motions in the z direction can be obtained from equations (2), (4), and (5).…”
Section: (8)mentioning
confidence: 99%
“…2 The introduction of this matrix reduces the stiness matrix into a banded block triangular one, i.e. via the shooting method, the equilibrium conditions of each nodal point (or a group of nodal points) can be considered singly.…”
Section: Introductionmentioning
confidence: 99%